Situating G. I. Gurdjieff's Meetings With Remarkable Men - Karalis, Vrasidas (Journal for the academic study of religion, 2014)
G.I. Gurdjieff's masterwork, Meetings with Remarkable Men (published posthumously in 1963), the second part of his All and Everything series, is probably one of the least studied books in the field of spiritual literature and has never been approached in regards to its literary structure. While the personality of its writer has monopolised the interest of most scholars, and the veracity of what is described in its pages has become the permanent obsession of many readers, the book itself as narrative structure, dialogic form and autobiographical self-revealing has remained a mystery and a veritable cryptogram. This article is focused around the dialogic form of the book and excavates its literary texture in order to frame the semantic centres of its discourse. Gurdjieff's serpentine prose aspires in recapturing implied rituals and modes of wordless interaction. It is constructed around forms of ritualistic unfolding of words circumscribing the core of an argument without ever articulating it, reinventing the literary tropes of the travel-writing genre. The absent yet ubiquitous enunciation of the semiotic centre is the most significant aspect of this narrative. This article briefly analyses the generic keys of Gurdjieff's prose and delineates his attempt to create space for pre-verbal, and occasionally post-verbal, self-presentation.